2005
DOI: 10.1079/bjn20051592
|View full text |Cite
|
Sign up to set email alerts
|

‘Glucose control-related’ and ‘non-glucose control-related’ effects of insulin on weight gain in newly insulin-treated type 2 diabetic patients

Abstract: Insulin use is common in type 2 diabetes and is frequently accompanied by weight gain, the composition of which is poorly understood. The present study evaluates insulin-induced body composition changes. Body weight and composition of thirty-two type 2 diabetic patients undergoing their first 12 months of insulin therapy were compared with those observed in thirty-two type 2 diabetic patients previously treated on insulin (minimum 1 year). Body composition was determined by simultaneous body water spaces (bioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Only one recently published trial, by Lane and colleagues, found a 5.3 kg weight loss after 24 weeks in 21 extremely obese (BMI 39.6 kg/m 2 ) patients with insulin-resistant type 2 diabetes [19]. The larger weight loss observed in the present study may be explained first by the fact that it was not designed with the intention to improve glycaemic control, as improvement in glycaemic control is usually associated with weight gain [5,8]. Second, liraglutide-induced insulin dose reductions were greater in our study than in others [17,19,23,[25][26][27], and the decrease in insulin dose was also a predictor of weight loss.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Only one recently published trial, by Lane and colleagues, found a 5.3 kg weight loss after 24 weeks in 21 extremely obese (BMI 39.6 kg/m 2 ) patients with insulin-resistant type 2 diabetes [19]. The larger weight loss observed in the present study may be explained first by the fact that it was not designed with the intention to improve glycaemic control, as improvement in glycaemic control is usually associated with weight gain [5,8]. Second, liraglutide-induced insulin dose reductions were greater in our study than in others [17,19,23,[25][26][27], and the decrease in insulin dose was also a predictor of weight loss.…”
Section: Discussionmentioning
confidence: 37%
“…This is obviously undesirable in an already overweight population, and it may lead to aversion to the therapy and a further increase in insulin dose, and offset the beneficial effects of insulin [6]. Most insulin-induced weight gain, on average 2-6 kg, occurs within the first 9-12 months of insulin therapy [5,7,8]. Hence, a therapy that ameliorates pronounced weight gain when encountered within this time frame would be extremely desirable, but the best treatment strategy for this clinical problem is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…7 The inherent anabolic activity of insulin on both adipose and muscle tissue may be responsible for prolonged periods of weight gain, even beyond the initial phase of "glucose control-related' weight gain, or re-gain. 88 So-called "defensive snacking" behaviors, driven by fears of hypoglycemia, can also contribute to weight gain in patients using insulin.…”
Section: Weight Gainmentioning
confidence: 99%
“…6,[87][88][89] Weight gain in type 2 patients occurs through increases in both fat and fat-free mass. 88,89 In the DCCT, even modest weight increases had a negative impact on lipid profiles and systolic blood pressure. 90 Similar findings in type 2 patients were noted in a report from the Swedish National Diabetes Register.…”
Section: Weight Gainmentioning
confidence: 99%
“…Percentage fat was calculated using a three-compartmental model (Siri, 1961), a model already validated in those with type 2 diabetes (Sallé et al 2005), which provides an assessment of percentage fat that is independent of FFM hydration:…”
Section: Statistical Analysis and Body Composition Calculationsmentioning
confidence: 99%